Do employees profit from profit sharing? Evidence from Canadian panel data - Richard J. Long; Tony Fang (Institute for the Study of Labor (IZA), 2012)
Using panel data from a large sample of Canadian establishments, this paper examines whether employee earnings increase, decrease, or do not change in the period subsequent to adoption of profit sharing, relative to establishments that do not adopt profit sharing. Our research contributes to knowledge by utilizing longitudinal analysis to assess the effects of profit sharing adoption on employee earnings growth within a carefully constructed sample of Canadian establishments, and by assessing both cash real earnings growth and total real earnings growth, while controlling for a wide array of variables that may affect these results. On average, employees in Canadian establishments that adopted profit sharing during 1999-2001 appeared to benefit from the introduction of profit sharing, in terms of both their cash real earnings growth and total real earnings growth, in the five-year span following introduction of profit sharing. This advantage was both statistically and practically significant, adding about 15 percentage points to real employee earnings growth over the five-year period, a period during which employee earnings growth was generally modest.
Keywords: J33; J31; J38; 330; profit sharing plans; employee earnings; firm-worker linked survey; Canada; Erfolgsbeteiligung; Arbeitskräfte; Einkommen; Schätzung; Dänemark